UV-microspectrophotometry: A method to prove wood modification with MMF?. (February 2015) - Mahnert, K.-C.; Adamopoulos, S.; Koch, G.; Militz, H.
Abstract : The modification of wood with methylolated melamine formaldehyde resin belongs to the group of impregnation modifications. In the course of this study, Koto sapwood samples were impregnated with methylolated melamine formaldehyde resin solutions in a full cell vacuum pressure process. The samples were cured at a maximum temperature of 120°C for 24 h. To characterise the modification, the solution uptake and weight percent gain of the samples were calculated. The fixation of the melamine as parameter for the degree of curing was examined by C/N analysis. Areal UV-microspectrophotometry scans of ultra-thin transverse sections of an untreated control and samples impregnated with methylolated melamine formaldehyde resin at 240 nm were recorded. Additionally, photometric point measurements with a spot size of 1 μm −2 in the range 230 and 350 nm were conducted. UV-microspectrophotometry was proven as suitable technique for the quantitative analysis of wood modified with methylolated melamine formaldehyde resin.